WOLFF-PARKINSON-WHITE SYNDROME AND ELECTROCARDIOGRAPHIC DIAGNOSIS: AN EXPANDED SUMMARY (CIPEEX, 2022)
WOLFF-PARKINSON-WHITE SYNDROME (WPW) IS A FORM OF ARRHYTHMIA CAUSED BY THE PRESENCE OF FIBERS THAT CARRY PRE-EXCITABLE SIGNALS DIRECTLY FROM THE ATRIUM TO THE VENTRICLE. THE OBJECTIVE OF THIS STUDY IS TO COMPARE THE ETIOLOGICAL AND ELECTROPHYSIOLOGICAL DIAGNOSIS OF WPW. THE SEARCH FOR ARTICLES IN THE PUBMED, CAMBRIDGE CORE, ACADEMIC AND SCIELO INDEXES WAS USED AS A METHODOLOGY TO CARRY OUT THE EXPANDED ABSTRACT. FROM THE ANALYSIS OF THE STUDIES OF PATIENTS DIAGNOSED WITH WPW IN THESE EXAMS, IT WAS POSSIBLE TO VERIFY THAT THE ECG IS LESS SAFE BECAUSE IT IS NOT AS SENSITIVE AND SPECIFIC FOR THE LOCATION OF THE ACCESSORY PATHWAYS AS THE FES.
Keywords: Wolff-Parkinson-White. Accessory roads. Delta waves.